LEADERSHIP OF SCHOOL EXECUTIVES OF RAT BURANA DISTRICT, BANGKOK - สวนแก้ว จรินทร์; สนเจริญ กัณฐนา; รัตนภักดี ชนะ; เหตระกูล ปรียาพร; สิมะกุลธร สุรพร (Thai Interdisciplinary and Sustainability Review, 2023)
This study aimed 1) to study attitude on leader’s role of executives of Rat Burana District, Bangkok and 2) to compare roles of leaders of school executives on personal factors which were gender, education, position and work experience. This study was a quantitative research. The example of the research was 354 teachers and school executives of six schools. The method used to collect data was questionnaire, analysis by using computer program. The Statistics used to analyze data were frequency, percentage, mean, standard deviation. t-test, and one way analysis. The research found that; 1) teachers and school committees had moderate level of opinion on roles of leaders of school executives. When each sector was examined in term of mean, it was found that the opinion of the respondents was at moderate level. These were opinion on role on coordination and evaluation, role on management and resource management, role on problem solving and negotiation as well as role on symbolic leaders or president of an organization. 2) For the comparison of opinion of teachers and school committees on roles of leader, it was found that those who had difference background of education, position and work experience share the same opinion.